Complaints and Procedures of Handling Complaints in Financial Institutions of Nepal - Upadhyay, Jitendra Prasad (NCC Journal, 2019)
Background - Complaint is a result of dissatisfaction or feeling of injustice/unfair treatment, related to his/her employment situation, which is formally filed and in written form. Objective – The objective of this paper is to examine the level of complaints that take place in the financial institutions of Nepal. Similarly, this study examines the causes and solutions of complaints in selected financial institutions. Methodology Used – Descriptive and analytical research designs have been used for the study. Primary data have been collected through the questionnaires using judgmental sampling from the financial institutions of Nepal. Questionnaires have been developed in five scales and mean, standard deviation and coefficient of variation have been used as tools. Findings – All the financial institutions have faced complaints from their employees and they try to resolve that complaints to their best.